Postcolonial developments;agriculture in the making of modern India - Gupta, Akhil (New Delhi, 1999)
This is a definitve study of what the postcolonial condition means to rural people in India. Focusing on the 'green revolution' of the 1960s, Akhil Gupta challenges the dichotomy of 'developed' and 'underdeveloped', as well as the notion of a monolithic postcolonial condition. Drawing links between village life, national trends and global forces, Gupta concludes with a discussion of the implications of environmentalism as exemplified by the Rio Earth Summit.
Keywords: Agriculture-India